Combination therapy with nisin, urolithin B, and vincristine exhibits synergistic antiproliferative and pro-apoptotic effects against human lymphoma cells: evidence from proteomics - Al-Khazaleh, Ahmad K.; Alsherbiny, Muhammad A.; Chang, Dennis; Münch, Gerald; Bhuyan, Deep Jyoti (Frontiers in Immunology, 2025)
Lymphoma remains a significant global health burden, necessitating innovative, targeted therapeutic strategies. Nisin (N), a bacteriocin produced by Lactococcus lactis, has demonstrated antimicrobial and anticancer properties through membrane disruption and apoptotic induction. Urolithin B (UB), a gut microbiota-derived metabolite of ellagitannins, has shown anti-inflammatory and antiproliferative activities in various cancer models. Vincristine (Vinc), a common anti-lymphoma drug, disrupts microtubule formation, leading to cell cycle arrest and apoptosis in cancer cells. This study explored the antiproliferative and pro-apoptotic effects of a triple combination therapy comprising N, UB, and Vinc against human lymphoma cell lines (HKB-11 and Hs 313.T). This study systematically evaluated the synergistic efficacy of both monotherapy and dual and triple combinations and molecular mechanisms using Alamar Blue viability assays, combination index (CI) modelling, reactive oxygen species (ROS) quantification, annexin V/7-AAD flow cytometry, and bottom-up label-free proteomics. The potential cytotoxicity of the combination on normal stromal HS-5 cells was also assessed using the Alamar Blue assay. The N: UB: Vinc combination at 2240: 210: 0.94 µM demonstrated potent synergy (CI values 0.31–0.50 at IC90 - IC95) and induced near-complete growth inhibition (> 99%) in both lymphoma cell lines with reduced toxicity (42.09 ± 1.21% viability) toward normal stromal HS-5 cells. ROS analysis revealed significant oxidative stress, while flow cytometry confirmed enhanced apoptosis (p < 0.0001) in the combination groups. Proteomic profiling of the combination N: UB: Vinc at 2450.94 µM uncovered distinct molecular responses, including upregulation of MAP1LC3B2 (Log2FC = 1.4), GMNN (Log2FC = 1.3), and SLC38A2 (Log2FC = 1.5), promoting apoptosis, cell cycle regulation, and mTOR signaling inhibition. Concurrently, key oncogenic and metabolic proteins were downregulated, including NNMT (Log2FC = –2.9), PLTP (Log2FC = –2.5), and CYP4X1 (Log2FC = –2.0), which implicated the suppression of MAPK-Akt signaling, ferroptosis activation, and lipid metabolism disruption. These results established a mechanistic rationale for combining postbiotics such as N and UB with standard chemotherapy, highlighting a promising avenue for safer and more effective lymphoma management in the future.